Virtual world for collaborative learning: a review - Abdul Rahman, Mohd. Hishamuddin (IEEE Computer Society, 2014)
Over the last century, rapid technological developments have substantially changed the landscape of the education world. As we can see today, most of the teaching and learning activities at all level of studies have been integrated with various forms of technologies, particularly with the Information and Communication Technology. This technology often relates to online learning, which usually involves the use of various forms of 2-dimensional applications. However, the recent times have seen many educational institutions around the globe shifting their interest towards the use of a new application for online learning, known as the virtual world. The virtual world has unique capabilities and unlike its 2-dimensional counterpart, it can generate a 3-dimensional social learning space, amplify the sense of presence and immersion of students, and support various forms of communications and interactions. Utilizing these capabilities with proper instructional strategies in conducting online learning activities can greatly enhance the online learning experience. Without a doubt, the virtual world has been considered as an important tool in modern education practice, especially for collaborative learning. To obtain a comprehensible view of this trend, this paper reviews some of the latest studies which have involved collaborative learning in virtual world. Four main topics were extracted from the reviewed studies: categories of virtual worlds, collaborative strategies used in the studies, focus of each study, and challenges of collaborative learning in virtual world.